A Comparison of Ultrasound Guided Curettage With and Without Uterine Artery Embolization on Controlling Intraoperative Blood Loss for a Cesarean Scar Pregnancy Treatment: Study Protocol for a Randomized Clinical Trial - Tang, Yunhui; Zhang, Yi; Tang, Hanqing; Che, Jiahui; Feng, Hua; Yao, Xiaoying; Chen, Qi (Frontiers in Endocrinology, 2021)
Introduction: Caesarean scar pregnancy affects 6% of all ectopic pregnancies in women with prior caesarean section and there is currently no consensus on the optimal treatment. Options of surgical treatment have a risk of intraoperative blood loss; therefore, uterine artery embolization (UAE) has been considered as an option of reducing intraoperative blood loss. However, UAE may be overused in clinical practice, especially in China. We present this protocol for a randomized clinical trial investigating the necessity of performing UAE for caesarean scar pregnancy, in combination with surgical suction curettage, taking into account the different subtypes of caesarean scar pregnancy. We recently developed a risk-scoring System (QRS) to estimate intraoperative blood loss, with 93.8% sensitivity and 6.3% false negative. Through this randomized clinical trial, we will retrospectively validate the QRS score on predicting intraoperative blood loss. Methods and analysis: We propose undertaking a randomised clinical trial sequentially recruiting 200 patients. All the patients will randomly receive ultrasound-guided curettage with or without UAE. Data on the subtypes of caesarean scar pregnancy (Type 1 and II and III) detected by ultrasound will be collected before operation. The score on estimating intraoperative blood loss assessed by our recently developed quantitative risk-scoring system (QRS) will be collected before the operation. We will primarily compare the duration of the operation, intraoperative blood loss and complications between the two groups. We will also retrospectively analyse the association of subtypes of caesarean scar pregnancy and the options of treatment and validate the QRS score. Outcomes of subsequent pregnancy within the 2-year follow-up will be secondary outcomes. Ethics and dissemination: The Hospital of Obstetrics & Gynaecology, Fudan University, China approved this study (Reference number KYY2020-185). Data will be presented at international conferences and published in peer-reviewed journals. Trial registration number: ChiCTR2100041654 Keywords: randomised clinical trial; caesarean scar pregnancy; uterine artery embolization; intraoperative blood loss; quantitative risk-scoring system